Feeding ecology of the Ethiopian wolf in the Simien Mountains National Park, Ethiopia. (30th July 2014) - Yihune, Mesele; Bekele, Afework
Abstract Feeding ecology of the Ethiopian wolf was studied in the Simien Mountains National Park, Ethiopia, during 2011–2012 using faecal analysis. A total of 214 faecal samples were collected from the study area. Data were analysed using descriptive statistics, and a chi‐square test was used to test seasonal differences in the frequency of prey item consumed. Percentage frequency of occurrence/scats and percentage frequency of occurrence/item were calculated. A Chesson index of prey preference was also calculated. Eight categories of prey items were identified from the Ethiopian wolf faecal samples. These comprised five species of rodents, sheep, birds and grass. Rodents occurred in most of the samples, and they were the most important prey items in their frequency of occurrence. Among the diurnal murid rodents (Arvicanthis abyssinicus, Lophuromys flavopunctatus and Otomys typus), A. abyssinicus (72%) was the most common species in the diet followed by L. flavopunctatus (24.3%). Arvicanthis abyssinicus was the most highly preferred prey item, with a Chesson index value of 0.3. There was no significant seasonal difference (χ2 = 2.03, d.f. = 1, P > 0.05) in the frequency of prey items recorded during the wet and dry seasons. As rodents are the main prey source of the Ethiopian wolf, they have to be protected to conserve the Ethiopian wolf in the study area.